Mammalian Target of Rapamycin Complex 2 Signaling Pathway Regulates Transient Receptor Potential Cation Channel 6 in Podocytes - Ding, Fangrui; Zhang, Xiaoyan; Li, Xuejuan; Zhang, Yanqin; Li, Baihong; Ding, Jie (PloS one, 2014)
Transient receptor potential cation channel 6 (TRPC6) is a nonselective cation channel, and abnormal expression and gain of function of TRPC6 are involved in the pathogenesis of hereditary and nonhereditary forms of renal disease. Although the molecular mechanisms underlying these diseases remain poorly understood, recent investigations revealed that many signaling pathways are involved in regulating TRPC6. We aimed to examine the effect of the mammalian target of rapamycin (mTOR) complex (mTOR complex 1 [mTORC1] or mTOR complex 2 [mTORC2]) signaling pathways on TRPC6 in podocytes, which are highly terminally differentiated renal epithelial cells that are critically required for the maintenance of the glomerular filtration barrier. We applied both pharmacological inhibitors of mTOR and specific siRNAs against mTOR components to explore which mTOR signaling pathway is involved in the regulation of TRPC6 in podocytes. The podocytes were exposed to rapamycin, an inhibitor of mTORC1, and ku0063794, a dual inhibitor of mTORC1 and mTORC2. In addition, specific siRNA-mediated knockdown of the mTORC1 component raptor and the mTORC2 component rictor was employed. The TRPC6 mRNA and protein expression levels were examined via real-time quantitative PCR and Western blot, respectively. Additionally, fluorescence calcium imaging was performed to evaluate the function of TRPC6 in podocytes. Rapamycin displayed no effect on the TRPC6 mRNA or protein expression levels or TRPC6-dependent calcium influx in podocytes. However, ku0063794 down-regulated the TRPC6 mRNA and protein levels and suppressed TRPC6-dependent calcium influx in podocytes. Furthermore, knockdown of raptor did not affect TRPC6 expression or function, whereas rictor knockdown suppressed TRPC6 protein expression and TRPC6-dependent calcium influx in podocytes. These findings indicate that the mTORC2 signaling pathway regulates TRPC6 in podocytes but that the mTORC1 signaling pathway does not appear to exert an effect on TRPC6.